2008
DOI: 10.1177/1524839908325066
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Examination of Perceptions of Physical Activity Guidelines and Preferences for Format

Abstract: A descriptive exploratory study was conducted to gain an understanding of public perceptions of physical activity guidelines and to discover what formats appeal to participants. Canada's Physical Activity Guide (CPAG) was used as an example of such guidelines. Data were collected from 22 participants in five focus groups (composed of female undergraduate students, female office workers, male office workers, participants in a Type II diabetes rehabilitation program, and participants in a cardiovascular rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 14 publications
2
32
0
Order By: Relevance
“…Criticisms of the previous Canadian PA Guidelines included a universal dislike for the cartoon-like format used to portray the information (Berry et al 2010). It has also been suggested that the guidelines be disseminated via Internet-based resources, with formatting that complements the stylistic and flashy design common in commercial, for-profit advertisements (Berry et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Criticisms of the previous Canadian PA Guidelines included a universal dislike for the cartoon-like format used to portray the information (Berry et al 2010). It has also been suggested that the guidelines be disseminated via Internet-based resources, with formatting that complements the stylistic and flashy design common in commercial, for-profit advertisements (Berry et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the guidelines be disseminated via Internet-based resources, with formatting that complements the stylistic and flashy design common in commercial, for-profit advertisements (Berry et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Involving end-users in the process may help identify strategies for persuasively communicating guidelines and developing related knowledge translation products that provide guidance on how to implement the guidelines (Latimer-Cheung et al 2013). To the best of our knowledge, published qualitative research examining stakeholder perceptions of existing guidelines has been conducted only after their release, including the Canadian Sedentary Behaviour Guidelines for the Early Years and UK Physical Activity and Sedentary Behaviour Guidelines (Bentley et al 2015), and Canada's Physical Activity Guide (Public Health Agency of Canada 1998) (Berry et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…25 Another recent study concluded that participants, including healthy young adults and older adults attending chronic disease rehabilitation programmes, were largely unaware of the Canadian Physical Activity Guidelines. 26 Given physiotherapists' expertise in prescribing exercise and promoting self-management of chronic diseases, 27 physiotherapists can enhance participants' understanding of exercise as self-care by explaining physiologic training principles and interpreting exercise guidelines, such as the Canadian Physical Activity Guidelines for Older Adults, 28 to help them get the most out of their efforts to exercise for health benefits.…”
Section: Discussionmentioning
confidence: 99%